Communication simulation with error correcting code using Matlab / Aubaidullahushalihin Muhamad - Muhamad, Aubaidullahushalihin (2009)
This project evaluates the performance of different type of error correcting code in an Additive White Gaussian Noise (AWGN) channel. Error control coding incorporates information into the signal that allows a receiver to find and correct bit error occurring in transmission and storage. Since such coding detects or correct errors incurred in the communication or storage channel, it is often referred to as channel coding. This project involves the design of a complete communication system. The error correcting codes that were used are Bose Chaudhuri-Hocquenghem code (BCH) and Hamming code. The BCH code and Hamming code are hard decision codes. The capability of these error correcting codes to detect and rectify error were assessed and evaluated. The maximum codeword length (N) used in the hamming code is 63 and the message length (K) is 57. For BCH code, the maximum N is 63, K is 36 and error-correction capability, t is 5.The results show that the best performance occurs when the communication system uses a BCH code with N=31, K=ll and t=5 with BPSK modulator/demodulator. The higher the values of N, K and t, the better the performance and in general BCH codes are better than Hamming code.